Leveraging Collaborative Strategic Reading (CSR) on Project-Based Learning (PjBL): Text Types - Unsiah, Frida; Suwarso, Pratnyawati Nuridi; Sujannah, Wahyu Diny; Adi, Sugeng Susilo; Damio, Siti Maftuhah (Journal of Languages and Language Teaching, 2024)
Reading is regarded as an essential activity in language learning, providing a valuable source of information, an exciting activity, a tool of communication, and a way to enhance one's knowledge. Collaborative Strategic Reading (CSR) is implemented in reading classes to enhance students' reading comprehension. The present study aimed to find out the correlation between students’ perceptions of Collaborative Strategic Reading (CSR) projects and their reading achievement. The participants of the study were 165 students of the second semester batch 2022/2023 taking a Reading Course in one of public universities in East Java Indonesia. The current study employed correlational design and the data were collected through a questionnaire consisting of four dimensions with 20 items adapted from Fan (2010). The dimensions were students’ general perceptions of CSR instruction, perceptions of implementation procedures of CSR, and views on their learning attitudes in CSR. The data on the students’ reading achievement were obtained through their TOEIC reading test, CSR project, midterm test, and final test scores. The data taken from students' perceptions of CSR and reading achievement were analyzed through Pearson Correlation coefficient. The result shows that the correlation between students’ perceptions of CSR and their reading achievement are highly significant. CSR encourages students to get involved actively in reading activities and increase their critical thinking to comprehend texts. Such experiences are beneficial for them which affect their perceptions of CSR towards their reading achievement.